Stress response in women mistreated by mate. An approach to its study - Laura López Angulo; Juan José Apollinaire Pennini; Marlen Array; Addis Moya Ávila (Medisur)
Background: Violence is a situation considered as a negative happening that causes an impact in the victim’s life, and alter his behavior and daily life, generating an equilibrium disturbance situation. Objective: To analize the stress response in women victims of violence in mate relationship. Method: An observational-analitic study was carried out of cases and controls. The sample was included 120 women; 40 cases and 80 controls, belonging to the Cienfuegos municipality in the year 2003. The variables used were: the cognitive valoration of the violent situation, the ways of confrontation, the locus control, the existence of familiar support, social support, and the influence on some health indicators. Results: It were statistically significant the differences in response to stress among the groups and its consecuences. Conclussions: Violence to women in mate relationship causes a high stress level, associated to confronting stiles directed to the emotions, these are interconnected to the external locus control and to the limitation of supportive perception, which are nocive to health.